DUST AND GENDER RELATED WITH LUNG VITAL CAPACITY DISSORDERS IN THE TEXTILE INDUSTRY SPINNING SECTION - Iwan Suryadi; Maria Paskanita Widjarnarti; Aditama Putra Nugraha; Hashfi Hawali Abdul Matin (Waste Technology, 2020)
Objective: Many factors affect lung function capacity in textile industry workers. This research aims to determine the factors that affect the vital role of pulmonary spinning workers in the textile industry. Methods: This research used an analytic observational research design with a cross-sectional approach. Sampling technique used total sampling and get the sample was 96 people, and measurement of lung vital capacity used spirometry. The Low Volume Sampler was applied to measure dust concentration, and the questionnaire was used to assess the individual characteristics. Results: Bivariate analysis of the variables is the working environment dust, and gender are significant. The result of multivariate analysis of dust is the most significant to the lung vital capacity. Conclusion: dust concentrations is classified above the Threshold Limit Value (TLV), so the company should to control the source of dust exposure.Keywords: lung vital capacity